THE CONTRIBUTION OF ADVERSITY QUOTIENT ON HIGH SCHOOL ACCELERATION LEARNING STUDENT AT JAKARTA - Anik Budi Utami; Lydia Freyani Hawadi (Universitas Gunadarma, 2006)
The aim of this study is know how far AQ has a contribution to academic achievement in accelerationclass students. This study is using a non-experimental design research and multiple regression. Thisstudy is using ARP’s Stotlz and already modified for students for acceleration class. The participants are73 acceleration class students. The results shows that there is no kontribution of the dimensions of AQ toacademic achievement in MIPA dan Bahasa.Key words: Adversity quotion, academic achievement, class acceleration